Prevalence and segregation analysis of dermoid sinus in Rhodesian Ridgebacks. (February 2022) - Distl, Ottmar
Highlights: Dermoid sinus is a complex genetic condition in Rhodesian Ridgebacks. Phenotypic selection decreases prevalence of dermoid sinus. Ridgeless Rhodesian Ridgebacks can also be affected by dermoid sinus. A joint dermoid sinus and ridge locus appears unlikely. Abstract: Rhodesian Ridgebacks are dogs with a characteristic dorsal hair ridge with backward-growing hair. Dermoid sinus was reported as a prevalent congenital condition in ridged dogs and as a sporadic finding in other dog breeds. This condition presents as a tubular skin indentation to variable degree into underlying tissues on the dorsal midline or cranial or caudal to the ridge. In the present study, data from 12, 700 puppies born to 1622 litter from Rhodesian Ridgebacks in 2001–2019 in Germany were analysed for the prevalence of dermoid sinus and ridgless animals. Data from litters with dogs segregating for dermoid sinus were used to test compatibility with an autosomal recessive Mendelian trait. Overall prevalence of dermoid sinus in 12, 700 puppies was 2.53%. In 1269 litter with only ridged animals, prevalence was 2.81%. In 46 litters, segregation of ridgeless dogs was observed, and two ridgeless animals had dermoid sinus. The overall trend for dermoid sinus prevalence significantly decreased by −0.099% per birth year, whereas a significant trend for ridgelessness was not found. A more complex genetic determination for dermoid sinus seems likely, due to the insufficient fit of a monogenic autosomal recessive model of inheritance and a heritability estimate of 0.78 ± 0.11. Genetic correlation with ridgelessness was −0.11. In conclusion, our data revealed a decreasing trend for the prevalence of dermoid sinus and a complex genetic basis for this condition. The ridge locus was unlikely to determine the expression of dermoid sinus, given the low segregation ratio for dermoid sinus in a population selected for the ridge allele.